Practical textbook of cardiac CT and MRI - Lim, Tae-Hwan (Springer Berlin Heidelberg Imprint: Springer, 2015)
This up-to-date textbook comprehensively reviews all aspects of cardiac CT and MRI and demonstrates the value of these techniques in clinical practice. A wide range of applications are considered, including imaging of atherosclerotic and non-atherosclerotic coronary artery disease, coronary revascularization, ischemic heart disease, non-ischemic cardiomyopathy, valvular heart disease, cardiac tumors, and pericardial disease. The numerous high-quality images illustrate how to interpret cardiac CT and MRI correctly for the purposes of diagnosis, treatment planning, and follow-up. Helpful summarizing sections in every chapter will facilitate rapid retrieval of information. This book will be of great value to radiologists and cardiologists seeking a reliable guide to the optimal use of cardiac CT and MRI in real clinical situations. An additional feature is the provision of QR codes allowing internet access to references, further figures, and motion pictures. The reader will be able to enjoy this book using a smartphone or tablet PC.